EVALUATION OF COST BENEFIT ANALYSIS AS A TOOL ON FINANCIAL PERFORMANCE OF SELECTED PUBLIC SUGAR FIRMS IN KENYA - Wanyonyi, Wasike Edward; Ronald, Dr. Martin Onsiro; Mindila, Dr. Robert; Mwiti, Dr. Evans (IJRDO - Journal of Applied Management Science, 2016)
There has been a lot of concern over rising operational costs across the globe and more soparticularly in Kenya due to energy costs, staff costs and even borrowing costs amongst manyothers. Sugar firms have over the last few years faced financial challenges causing uncertaintyand anxiety to key stakeholders within and outside the company. The problem for the researchwas the apparent high operational costs that continued being exhibited which resulted inlosses and therefore poor performance. The purpose of this study is to evaluate cost benefitanalysis tools on financial performance of selected public sugar firms in Kenya. The specificobjective of the study was to determine the extent of application of Cost-Benefit Analysis as atool on financial performance. On average, the cost of producing a ton of sugar was highest atUSD 870 and lowest at USD 300 in Kenya and Brazil which showed an extreme andunfavorable variance against sugar firms in Kenya of USD 570 (Eleventh Parliament,ThirdSession, 2015). The problem for the research was the apparent high operational costs thatwere being exhibited uncontrollably and which resulted in losses and therefore poor financialperformance of the selected public sugar companies in Kenya. Cost - Benefit Analysisprovides a means of appraising the future benefits in light of the costs that must be incurred inthe present and its purpose is to measure the expected benefits of the investment so as to guidein rational resource allocation (Woodhall, 2004). Amongst the many accounting – basedfinancial performance measurements are Return on Assets (ROA), Gross Profit Margin,Return On Investment (ROI) and Earnings Per Share (San & Heng, 2011). In the report ofCokins(2006), it stated that there was an overwhelming desire among firms to know welltheir costs and factors that drive them. It however found out that there is no clearunderstanding of the costs and the tools or methods to distinguish them. The reviewedliterature above does not show any work done on evaluation of Cost Benefit Analysis Toolson financial performance of corporate organizations. A mixed methodology was used because